PARADIGM OF AGRICULTURAL LAND USE ECONOMICS UNDER NEW LAND RELATIONS - Druhak, V. M. (Землеустрій, кадастр і моніторинг земель, 2012)
The paradigm of economy of agricultural land use in the conditions of the land relations, which consists in allocation in a separate field of activity of economic, ecological and egal relation of ownership of land of sujects of land use  and formations and regulations of these relations with application of the new institutional economic theory are proved.